2021
DOI: 10.1007/s41315-021-00200-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards reconfigurable and flexible multirotors

Abstract: Reconfigurable multirotors (RMs) with flexible frames and integrated mechanical compliance are increasingly explored to develop multifunctional aerial robots with high power-to-weight ratios. In this paper, we review the state-of-the-art research on RMs and classify them into three broad categories as tiltrotors, multimodal and foldable RMs. The RMs with the ability to arbitrarily orient their thrust by employing tilting rotors are classified as tiltrotors, the multirotors with multi modal locomotion capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…In the bottom-right quadrant, aerial robots with a limited DOF and requires high precision control is representative of classical rigid multicopters or fixedwing robots. In the top right quadrant, with an increasing number of DOFs that require high precision control, the design space shifts to highly adaptable, active, reconfigurable and foldable multi-rotors [19,20]. On the other end of the spectrum, the bottom-right quadrant, a lower DOF and less requirement for active control, leads to design of drones with PAI embodied adaptable bodies, such as soft bodied drones and passive foldable multi-rotors [3,[21][22][23].…”
Section: Nature Inspires the Adoption Of The Pai Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…In the bottom-right quadrant, aerial robots with a limited DOF and requires high precision control is representative of classical rigid multicopters or fixedwing robots. In the top right quadrant, with an increasing number of DOFs that require high precision control, the design space shifts to highly adaptable, active, reconfigurable and foldable multi-rotors [19,20]. On the other end of the spectrum, the bottom-right quadrant, a lower DOF and less requirement for active control, leads to design of drones with PAI embodied adaptable bodies, such as soft bodied drones and passive foldable multi-rotors [3,[21][22][23].…”
Section: Nature Inspires the Adoption Of The Pai Paradigmmentioning
confidence: 99%
“…As we will see throughout this paper, metamorphosis augments the functionalities of soft aerial platforms. From the capabilities of adapting their size to go through apertures, or to absorb impact, or to manipulate objects [3,19,33]. Metamorphosis is also highlighted in multi-modal transitions, from aerial to terrestrial environments [34,35] and aerial to aquatic environments [36,37].…”
Section: Nature Inspires the Adoption Of The Pai Paradigmmentioning
confidence: 99%
“…Proof: To analyze this case, consider a switched system generated by two dynamical systems such that P = [1,2]. Let t i < t j be two switching times when σ = 1.…”
Section: B Case With Model Uncertainties and No External Disturbancesmentioning
confidence: 99%
“…Foldable quadrotors (FQrs) have created a paradigm shift in the design of multirotor aerial vehicles for widening the scope of applications such as flying through small openings and cluttered spaces [1]. While there is ample research demonstrating the mechanical feasibility of the foldable designs [2], [3], limited literature exists on the analysis of the low-level flight controller and the effects of inflight configuration switching.…”
Section: Introductionmentioning
confidence: 99%
“…According to recent studies, 13 the reconfigurable multirotors can be divided as shown in Figure 1. In the paper, 4 a new reconfigurable quadcopter, which can change its mechanical structure, was presented.…”
Section: Introductionmentioning
confidence: 99%